8
$\begingroup$

In the article "The unruly $\sin (\pi/7)$ of Samuel Moreno, the following infinite product is given: enter image description here

Also, the same article shows that $\sin (\pi/7)$ is equal to the infinite nested radical

$ \sin (\pi/7) = \frac{1}{2}\sqrt{2 - \sqrt{2 - \sqrt{2 - \sqrt{2 + \sqrt{2 - \sqrt{2 - \sqrt{2 + \sqrt{2 - \sqrt{2 - \sqrt{2+...}}}}}}}}}}$

The question is: are these two expressions fundamentally different for $\sin(\pi/7)$, or is it possible to rewritte the infinite nested radical into that infinite product by simple algebraic manipulations?

$\endgroup$
  • $\begingroup$ Are you sure that it's $$\sin\dfrac {\pi}7=\dfrac 12\sqrt{2-\sqrt{2-\sqrt{2-\sqrt{2+\sqrt{2-\sqrt{2-\sqrt{2+\sqrt{2-\sqrt{2-\sqrt{2+\cdots}}}}}}}}}}\tag1$$And not$$\sin\dfrac {\pi}7=\dfrac 12\sqrt{2-\sqrt{2-\sqrt{2+\sqrt{2-\sqrt{2-\sqrt{2+\sqrt{2-\sqrt{2-\sqrt{2+\cdots}}}}}}}}}\tag2$$ $\endgroup$ – Frank Jan 8 '17 at 17:48
  • $\begingroup$ No, the expression $(1)$ is correct. $\endgroup$ – C.C. Babock Jan 9 '17 at 17:25
3
$\begingroup$

Let: $$ \begin{align} \LARGE{\rho}\normalsize &= \left(\small \sqrt{2} \,\sqrt{2-\sqrt{2}} \,\sqrt{2+\sqrt{2-\sqrt{2}}} \normalsize\right) \times \\[2mm] & \space \left(\small \sqrt{2\color{red}{-}\sqrt{2+\sqrt{2-\sqrt{2}}}} \,\sqrt{2\color{red}{-}\sqrt{2-\sqrt{2+\sqrt{2-\sqrt{2}}}}} \,\color{red}{\sqrt{2+ \color{black}{\sqrt{2-\sqrt{2-\sqrt{2+\sqrt{2-\sqrt{2}}}}}}}} \normalsize\right) \times \cdots \\[4mm] \LARGE{\sigma}\normalsize &= \color{red}{\sqrt{2- \color{black}{\sqrt{2-\sqrt{2-\sqrt{2+\sqrt{2-\sqrt{2-\sqrt{2+\sqrt{\cdots}}}}}}}}}} \space\space\small\{\text{Same as last item of}\,\rho\,\text{with minus sign}\} \end{align} $$ Fundamentally, the two expressions are the same.
And to transpose between them, we use the property: $$ \boxed{ \quad \color{red}{\Large{\rho \cdot \sigma = 2}} \quad } \\[4mm] \frac{1}{\rho} = \frac{1}{\rho} \color{red}{\cdot \frac{\sigma}{\sigma}} = \frac{\sigma}{\rho\cdot\sigma} = \frac{\sigma}{2} = \quad\sin\left(\frac{\pi}{7}\right)\quad = \frac{\sigma}{2} = \frac{\sigma}{2} \color{red}{\cdot \frac{\rho}{\rho}} = \frac{\rho\cdot\sigma/2}{\rho} = \frac{1}{\rho} $$
In order to trace the simplifying process, let us consider the definition of both $\left(\large{\rho}\right)$ and $\left(\large{\sigma}\right)$ upto $n$,
Where $\left(\large{\rho}\right)$ definition is consist of three square-roots at a time, as illustrated above: $$ \begin{align} \LARGE{\rho}\normalsize &= \left(\large{\rho}_{\normalsize 0}\,\large{\rho}_{\normalsize 1}\,\large{\rho}_{\normalsize 2}\right) \left(\large{\rho}_{\normalsize 3}\,\large{\rho}_{\normalsize 4}\,\large{\rho}_{\normalsize 5}\right) \cdots \left(\large{\rho}_{\normalsize 3n-3}\,\large{\rho}_{\normalsize 3n-2}\,\large{\rho}_{\normalsize 3n-1}\right) \left(\large{\rho}_{\normalsize 3n}\,\large{\rho}_{\normalsize 3n+1}\,\large{\rho}_{\normalsize 3n+2}\right) \\[2mm] &= \left(\large{\rho}_{\normalsize 0}\,\large{\rho}_{\normalsize 1}\,\large{\rho}_{\normalsize 2}\right) \left(\large{\rho}_{\normalsize 3}\,\large{\rho}_{\normalsize 4}\,\large{\rho}_{\normalsize 5}\right) \cdots \left(\large{\rho}_{\normalsize 3n-3}\,\large{\rho}_{\normalsize 3n-2}\,\large{\rho}_{\normalsize 3n-1}\right) \left(\sqrt{2\color{red}{-}\rho_{\small 3n-1}}\,\sqrt{2\color{red}{-}\rho_{\small 3n}}\,\sqrt{2\color{red}{+}\rho_{\small 3n+1}}\right) \end{align} $$ And $\left(\large{\sigma}\right)$ equals same as last item of $\large{\rho}\,$ with minus sign, as mentioned above: $$ \LARGE{\sigma}\normalsize = \sqrt{2\color{red}{-}\rho_{\small 3n+1}} \qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad $$ So: $$ \begin{align} & \left(\large{\rho}_{\normalsize 3n}\,\large{\rho}_{\normalsize 3n+1}\,\large{\rho}_{\normalsize 3n+2}\right) \,\sqrt{2-\rho_{\small 3n+1}} \\[2mm] & \qquad = \sqrt{2-\rho_{\small 3n-1}}\,\sqrt{2-\rho_{\small 3n}}\,\sqrt{2+\rho_{\small 3n+1}}\,\sqrt{2-\rho_{\small 3n+1}} = \sqrt{2-\rho_{\small 3n-1}}\,\sqrt{2-\rho_{\small 3n}}\,\sqrt{4-\rho_{\small 3n+1}^2} \\[2mm] & \qquad = \sqrt{2-\rho_{\small 3n-1}}\,\sqrt{2-\rho_{\small 3n}}\,\sqrt{4-\left(2-\rho_{\small 3n}\right)} = \sqrt{2-\rho_{\small 3n-1}}\,\sqrt{4-\rho_{\small 3n}^2} \\[2mm] & \qquad = \sqrt{2-\rho_{\small 3n-1}}\,\sqrt{4-\left(2-\rho_{\small 3n-1}\right)} = \sqrt{4-\rho_{\small 3n-1}^2} = \sqrt{4-\left(2+\rho_{\small 3n-2}\right)} = \color{red}{\sqrt{2-\rho_{\small 3n-2}}} \end{align} $$ Thus: $$ \begin{align} \color{red}{\Large{\rho \cdot \sigma}}\normalsize &= \left[\left(\large{\rho}_{\normalsize 0}\,\large{\rho}_{\normalsize 1}\,\large{\rho}_{\normalsize 2}\right) \left(\large{\rho}_{\normalsize 3}\,\large{\rho}_{\normalsize 4}\,\large{\rho}_{\normalsize 5}\right) \cdots \left(\large{\rho}_{\normalsize 3n-3}\,\large{\rho}_{\normalsize 3n-2}\,\large{\rho}_{\normalsize 3n-1}\right) \left(\large{\rho}_{\normalsize 3n}\,\large{\rho}_{\normalsize 3n+1}\,\large{\rho}_{\normalsize 3n+2}\right)\right]\,\sqrt{2-\large{\rho}_{\normalsize 3n+1}} \\[2mm] &= \left[\left(\large{\rho}_{\normalsize 0}\,\large{\rho}_{\normalsize 1}\,\large{\rho}_{\normalsize 2}\right) \left(\large{\rho}_{\normalsize 3}\,\large{\rho}_{\normalsize 4}\,\large{\rho}_{\normalsize 5}\right) \cdots \left(\large{\rho}_{\normalsize 3n-3}\,\large{\rho}_{\normalsize 3n-2}\,\large{\rho}_{\normalsize 3n-1}\right)\right]\,\sqrt{2-\large{\rho}_{\normalsize 3n-2}} \\[2mm] &= \left[\left(\large{\rho}_{\normalsize 0}\,\large{\rho}_{\normalsize 1}\,\large{\rho}_{\normalsize 2}\right) \left(\large{\rho}_{\normalsize 3}\,\large{\rho}_{\normalsize 4}\,\large{\rho}_{\normalsize 5}\right) \cdots \right]\,\sqrt{2-\large{\rho}_{\normalsize 3n-5}} \\[2mm] &= \quad \cdots \quad \cdots \quad \cdots \\[2mm] &= \left[\left(\large{\rho}_{\normalsize 0}\,\large{\rho}_{\normalsize 1}\,\large{\rho}_{\normalsize 2}\right)\right]\,\sqrt{2-\large{\rho}_{\normalsize 1}} = \large{\rho}_{\normalsize 0}\normalsize\,\sqrt{4-\rho_{\small 0}^2} \normalsize = \sqrt{2}\,\sqrt{4-2} = \color{red}{2 \quad \forall\space n \ge 1} \end{align} $$ Hence: $$ \lim_{n\rightarrow\infty}\frac{1}{\rho} = \lim_{n\rightarrow\infty}\frac{\sigma}{2} = \sin\left(\frac{\pi}{7}\right) \quad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad $$


In order use this technique in general, for a period of length $\color{red}{m}$, we have: $$ \begin{align} \color{red}{{\large\rho}_{-1}=0},\,\, {\large\rho}_{0} &= \sqrt{2\pm{\rho}_{-1}},\,\, {\large\rho}_{1}=\sqrt{2\pm{\rho}_{0}},\,\, {\large\rho}_{2}=\sqrt{2\pm{\rho}_{1}},\,\, \cdots ,\,\, {\large\rho}_{m-1}=\sqrt{2\pm{\rho}_{m-2}},\,\, \cdots \\[2mm] {\Large\rho} &= \prod_{k=0}^{n}\left( {\large\rho}_{mk}\, {\large\rho}_{mk+1}\, \cdots\, {\large\rho}_{mk+m-2}\, {\large\rho}_{mk+m-1} \right) \qquad \\[2mm] &= \prod_{k=0}^{n}\left( \sqrt{2\pm{\large\rho}_{mk-1}}\, \sqrt{2\pm{\large\rho}_{mk}}\, \cdots\, \sqrt{2\pm{\large\rho}_{mk+m-3}}\, \sqrt{2\color{red}{\pm}{\large\rho}_{mk+m-2}} \right) \\[2mm] {\Large\sigma} &= \sqrt{2\color{red}{\mp}{\large\rho}_{mn+m-2}} \end{align} $$ Hence, $\,\left({\large\sigma}\right)\,$ must start with a different sign from the actual period!
Nevertheless, if $\,{\large\sigma}\,$ is not comply with this condition, we still have options to write the product form of related/equivalent function by applying simple manipulations to the original $\,{\large\sigma}\,$.

Consider the following example $\left\{\,\text{period}\,\left(+,+,-,-,-\right)\,\right\}$: $$ \begin{align} \cos\left(\frac{\pi}{11}\right) &= \frac12\,\sqrt{2\color{red}{+}\sqrt{2+\sqrt{2-\sqrt{2-\sqrt{2-\sqrt{2\color{blue}{+}\sqrt{\cdots}}}}}}} \\[2mm] \implies \qquad &\space \underbrace{\color{red}{+}{\large/}+,-,-,-,} \underbrace{\color{blue}{+}{\large/}+,-,-,-,} \underbrace{\color{blue}{+}{\large/}+,-,-,-,} \color{blue}{+}{\large/}\cdots \end{align} $$ And as it appears, after isolating the first sign, the pattern is not obeying the condition.
We have two options to convert it into applicable format: $$ \color{blue}{\underline{\left({\bf1}\right) - \,\text{Convert to}\, \sin(\pi/11)}} \space\quad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad \\[2mm] \begin{align} \sin\left(\frac{\pi}{11}\right) &= \sqrt{1-\cos^2\left(\frac{\pi}{11}\right)} = \frac12\,\sqrt{4-\left[2\cos\left(\frac{\pi}{11}\right)\right]^2} \Rightarrow \\[2mm] \sin\left(\frac{\pi}{11}\right) &= \frac12\,\sqrt{2\color{red}{-}\sqrt{2+\sqrt{2-\sqrt{2-\sqrt{2-\sqrt{2\color{blue}{+}\sqrt{\cdots}}}}}}} \\[2mm] \implies \qquad &\space \underbrace{\color{red}{-}{\large/}+,-,-,-,} \underbrace{\color{blue}{+}{\large/}+,-,-,-,} \underbrace{\color{blue}{+}{\large/}+,-,-,-,} \color{blue}{+}{\large/}\cdots \\[2mm] \end{align} \\[2mm] {\Large\rho} = \prod_{k=0}^{n}\left( \sqrt{2-{\large\rho}_{5k-1}}\, \sqrt{2-{\large\rho}_{5k\space\space\space\space}}\, \sqrt{2-{\large\rho}_{5k+1}}\, \sqrt{2+{\large\rho}_{5k+2}}\, \sqrt{2\color{red}{+}{\large\rho}_{5k+3}} \right) \\[2mm] {\Large\sigma} = \sqrt{2\color{red}{-}{\large\rho}_{5n+3}}\,,\quad {\Large\rho}\cdot{\Large\sigma}=2\,,\quad \sin\left(\frac{\pi}{11}\right)=\frac{{\large\sigma}}{2}=\frac{1}{{\large\rho}}\,,\quad \cos\left(\frac{\pi}{11}\right)=\sqrt{1-\left(1/{\large\rho}\right)^2} \\[4mm] $$ $$ \color{blue}{\underline{\left({\bf2}\right) - \,\text{Convert to}\, \cos(\pi/22)}} \space\quad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad\qquad \\[2mm] \begin{align} \cos\left(\frac{\pi}{22}\right) &= \sqrt{\frac12+\frac12\,\cos\left(\frac{\pi}{11}\right)} = \frac12\,\sqrt{2+2\,\cos\left(\frac{\pi}{11}\right)} \Rightarrow \\[2mm] \cos\left(\frac{\pi}{22}\right) &= \frac12\,\sqrt{2\color{red}{+}\sqrt{2+\sqrt{2+\sqrt{2-\sqrt{2-\sqrt{2\color{blue}{-}\sqrt{\cdots}}}}}}} \\[2mm] \implies \qquad &\space \underbrace{\color{red}{+}{\large/}+,+,-,-,} \underbrace{\color{blue}{-}{\large/}+,+,-,-,} \underbrace{\color{blue}{-}{\large/}+,+,-,-,} \color{blue}{-}{\large/}\cdots \\[2mm] \end{align} \\[2mm] {\Large\rho} = \prod_{k=0}^{n}\left( \sqrt{2-{\large\rho}_{5k-1}}\, \sqrt{2-{\large\rho}_{5k\space\space\space\space}}\, \sqrt{2+{\large\rho}_{5k+1}}\, \sqrt{2+{\large\rho}_{5k+2}}\, \sqrt{2\color{red}{-}{\large\rho}_{5k+3}} \right) \\[2mm] {\Large\sigma} = \sqrt{2\color{red}{+}{\large\rho}_{5n+3}}\,,\quad {\Large\rho}\cdot{\Large\sigma}=2\,,\quad \cos\left(\frac{\pi}{22}\right)=\frac{{\large\sigma}}{2}=\frac{1}{{\large\rho}}\,,\quad \cos\left(\frac{\pi}{11}\right)=\sqrt{\frac12+\frac12\,\left(1/{\large\rho}\right)} \\[2mm] $$ And here are Mathematica codes for these two options:


n = 4;
r = 1; e = 0; For[k = 0, n >= k, k++, {a = Sqrt[2 - e]; b = Sqrt[2 - a]; c = Sqrt[2 - b]; d = Sqrt[2 + c]; e = Sqrt[2 + d]; r = r (a b c d e)}];
s = 1; x = Sqrt[2 + Sqrt[2 - Sqrt[2 - Sqrt[2]]]]; For[k = 0, (n - 1) >= k, k++, {x = Sqrt[2 + Sqrt[2 - Sqrt[2 - Sqrt[2 - Sqrt[2 + x]]]]]}]; s = Sqrt[2 - x];
Print[N[r s], "  ", N[1/r], "  ", N[s/2], "  ", N[Sin[Pi/11]]]

n = 4;
r = 1; e = 0; For[k = 0, n >= k, k++, {a = Sqrt[2 - e]; b = Sqrt[2 - a]; c = Sqrt[2 + b]; d = Sqrt[2 + c]; e = Sqrt[2 - d]; r = r (a b c d e)}];
s = 1; x = Sqrt[2 + Sqrt[2 + Sqrt[2 - Sqrt[2]]]]; For[k = 0, (n - 1) >= k, k++, {x = Sqrt[2 + Sqrt[2 + Sqrt[2 - Sqrt[2 - Sqrt[2 - x]]]]]}]; s = Sqrt[2 + x];
Print[N[r s], "  ", N[1/r], "  ", N[s/2], "  ", N[Cos[Pi/22]]]

$\endgroup$
  • $\begingroup$ @HazemOrahi +1 Very clever analysis. Is it possible to use the above procedure to transform this type of infinite radicals into infinite products? For example, $\cos \frac{\pi}{11} = \frac{1}{2}\sqrt{2 + \sqrt{2 + \sqrt{2 - \sqrt{2 - \sqrt{2 - \sqrt{2 + ...}}}}}}$ with period $(+, +, -, -, -)$. Can this be easily transformed into an infinite product, let's say $1/\rho$? $\endgroup$ – C.C. Babock Jan 9 '17 at 17:23
  • $\begingroup$ I want to say @HazemOrabi $\endgroup$ – C.C. Babock Jan 9 '17 at 18:16
  • $\begingroup$ @C.C.Babock: Thanks a lot. I’ll check your proposition and get back to you soon. $\endgroup$ – Hazem Orabi Jan 9 '17 at 22:30
  • $\begingroup$ OK. I'll wait . $\endgroup$ – C.C. Babock Jan 11 '17 at 18:03
  • 1
    $\begingroup$ @C.C.Babock: I edited the answer to include a sufficient condition for the technique to work in the general case. Nevertheless, I tried my best to find a direct infinite product for $\,\sigma\,$ of $\,\cos(\pi/11)\,$ but, unfortunately, the condition of having a different sign to start $\,\sigma\,$ with seems to be almost forced! Thanks again & good luck. $\endgroup$ – Hazem Orabi Jan 11 '17 at 22:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.